The Maxim of Order from Teachers’ Perspective - Kandel, Ganesh Kumar (Journal of NELTA Surkhet, 2018)
This article reports the perception of teachers towards the maxim of order. It also tries to reflect the teachers’ classroom behaviours or culture of teaching. It is physical reflection of their maxim that they have developed in their mind about different aspects of ELT. The researcher used classroom observation and interview as research tools. Ten teachers were the respondents in this study. These ten teachers were interviewed and three classes of each teacher were observed to obtain required information. Most of the respondents reported that they prefer calm, peaceful, ordered and disciplined classes. They provided several reasons to support their views. They expressed their positive and supporting view towards the maxim of order. The disciplined and ordered classroom is justified in this research. They argued that disciplined and ordered classroom assists the teachers to conduct their activities in comfortable way in the classroom and assists students to grasp what teacher offers them. Journal of NELTA Surkhet, Vol. 5 January, 2018